2020
DOI: 10.1007/s11869-020-00847-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-variance nexus between COVID-19 mortality, humidity, and air quality index in Wuhan, China: New insights from partial and multiple wavelet coherence

Abstract: The worldwide outbreak of COVID-19 disease has caused immense damage to our health and economic and social life. This research article helps to determine the impact of climate on the lethality of this disease. Air quality index and average humidity are selected from the family of climate variables, to determine its impact on the daily new cases of COVID-19-related deaths in Wuhan, China. We have used wavelet analysis (wavelet transform coherence (WTC), partial (PWC), and multiple wavelet coherence (MWC), due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 34 publications
9
84
1
2
Order By: Relevance
“…In addition, many of these studies only considered meteorological factors, which limits the reliability of their results. We also acknowledge that air quality index (AQI) is an important factor for many respiratory infectious diseases, as bad air quality led to increased mortality in the city of Wuhan [24]. The weather can also affect the AQI directly, as rainfall reduces atmospheric pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of these studies only considered meteorological factors, which limits the reliability of their results. We also acknowledge that air quality index (AQI) is an important factor for many respiratory infectious diseases, as bad air quality led to increased mortality in the city of Wuhan [24]. The weather can also affect the AQI directly, as rainfall reduces atmospheric pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The tourism sector will be badly damaged, and if COVID-19 does not finish by the end of this summer, Turkey will lose the place of 50 million visitors and $34.5 billion income (Institute TTS 2020a ). The only positive impact of COVID-19 is the improved air environment, as suggested by recent research (Gautam 2020 ; Shahzad et al 2020 ; Fareed et al 2020 ). In this regard, Gautam ( 2020 ) denoted that due to COVID-19, global air pollution is significantly reduced and the natural environment gains additional benefits.…”
Section: Literature Reviewmentioning
confidence: 80%
“…The role of climate variables on the daily new cases of COVID-19 related deaths was explored in the origin city of the pandemic i.e. Wuhan and found a significant correlation between AQI, humidity, and mortality (Fareed et al, 2020). Similarly, Zhang et al (2020) threw light on the total effect of ambient temperature and air quality on COVID-19 transmission in China and indicated that rising temperature restricted deterioration of air quality which in turn reduced disease transmission.…”
Section: Accepted Manuscriptmentioning
confidence: 99%